2020
DOI: 10.1042/bsr20191265
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA GHET1 promotes cervical cancer progression through regulating AKT/mTOR and Wnt/β-catenin signaling pathways

Abstract: Cervical cancer (CC) is a prevalent gynecological cancer, and the patients with CC usually suffer from dismal prognosis. Long non-coding RNAs (lncRNAs) are demonstrated to serve as promising biological targets in human cancers. Gastric carcinoma proliferation enhancing transcript 1 (GHET1) has been revealed to function as an oncogene in several cancers, but it has never been investigated in CC. We proposed to examine the biological role of GHET1 in CC and the underlying mechanism and validated the up-regulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 26 publications
1
18
0
Order By: Relevance
“…CC cells. 28 In the current study, we found that lncRNA MIR4435-2HG knockdown suppressed the viability, migration ability and invasion ability of CC cells. Similar to our results, a recent study has demonstrated that the proliferation, invasion and migration of CRC cells can be inhibited by MIR4435-2HG knockdown.…”
mentioning
confidence: 49%
“…CC cells. 28 In the current study, we found that lncRNA MIR4435-2HG knockdown suppressed the viability, migration ability and invasion ability of CC cells. Similar to our results, a recent study has demonstrated that the proliferation, invasion and migration of CRC cells can be inhibited by MIR4435-2HG knockdown.…”
mentioning
confidence: 49%
“…Previous studies have shown that activation of the Wnt signaling pathway is the first step in carcinogenesis of the cervix ( Uren et al, 2005 ). The Wnt signaling pathway regulates proliferation, migration, and chemoradiation tolerance in cervical cancer cells and is associated with poor clinical outcomes ( Bahrami et al, 2017 ; Yang et al, 2018 ; Liu et al, 2020d ). Drews et al (2019) found that E6 degrades NHERF1 to regulate the Wnt signaling pathway and affect the progression of cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the previous research on IGF2BP2 has focused on its role as a retinol-binding protein (RBP) targeting downstream transcription factors to regulate post-transcriptional translational carcinogenesis. In cervical cancer, gastric carcinoma proliferation enhancing transcript 1 (GHET1) regulates AKT/mTOR and Wnt/β-catenin signaling pathways by stabilizing the interaction of E2F6 and IGF2BP2 (Liu et al, 2020). Non-coding genes can also target IGF2BP2 directly: the lncRNA HOTAIR inhibits IGF2BP2 and regulates colon cancer growth and invasion (Wu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%